Managed confrontation and the managed heart: gendered teacher talk through reported speech. Issue 2 (4th May 2018) - LeBlanc, Robert Jean
Abstract: Based on data drawn from audio recordings of a 9th grade female English teacher in Southern California and her interactions with students in her classroom, I examined how she represents the thinking and voices of her students as her students during confrontation and conflict. Analysis demonstrates how the projected ventriloquation of her students' thinking and voices becomes a resource for indirectness in interaction, and a means to manage the gendered contradictions of teaching – the simultaneous expectations that female teachers provide authoritative criticism of student work while also being emotionally supportive – in the back-and-forth of classroom talk. In this analysis, I contribute to an understanding of intertextuality and reported speech in teacher talk, including the relevance of emotional labour, and demonstrate how a teacher uses the linguistic resources of the 'managed heart' to mediate conflict and criticism in whole-class interactions.